2012
DOI: 10.1002/mma.2632
|View full text |Cite
|
Sign up to set email alerts
|

Hardy–Sobolev derivatives of phase and amplitude, and their applications

Abstract: Communicated by I. T. LeongIn time-frequency analysis, there are fundamental formulas expressing the mean and variance of the Fourier frequency of signals, s, originally defined in the Fourier frequency domain, in terms of integrals against the density js.t/j 2 in the time domain. In the literature, the existing formulas are only for smooth signals, for it is the classical derivatives of the phase and amplitude of the signals that are involved. The two representations of the covariance also rely on the classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…The assumption of the zero value of the new derivatives at the points is conventional that makes the proofs going. A detailed analysis and comprehensive development of relations of several types of derivatives with applications in signal analysis are given in [5], [7] and [6].…”
Section: B Properties Of Signal Moments In the Lct Domain And Other mentioning
confidence: 99%
See 1 more Smart Citation
“…The assumption of the zero value of the new derivatives at the points is conventional that makes the proofs going. A detailed analysis and comprehensive development of relations of several types of derivatives with applications in signal analysis are given in [5], [7] and [6].…”
Section: B Properties Of Signal Moments In the Lct Domain And Other mentioning
confidence: 99%
“…To solve this problem, [6]- [8] work with different types of derivatives, viz., Hardy-Sobolev derivative, derivatives as non-tangential boundary limits and Fourier transform derivative, etc., through Hardy decomposition and Fourier transformation. We showed that under certain conditions the various types of derivatives can be unified.…”
Section: Introductionmentioning
confidence: 99%
“…We prove in [7] that when the derivatives ϕ (t), s (t) and ρ (t) exist in the classical sense, then the Hardy-Sobolev derivatives ϕ * (t), s * (t) and ρ * (t) coincide with them. A large number of relations for smooth signals are extendable to general functions in the Sobolev space by using Hardy-Sobolev derivatives ( [7]). The frequency spectra or inverse Fourier transforms, respectively for the discrete or continuous allpass filters and signals of minimum phase, are themselves analytic signals.…”
Section: Edics: Dsp-tfsr Dsp-bank I Introductionmentioning
confidence: 94%
“…Now, we recall the definition of HS derivative for a signal fL12(double-struckR;double-struckC)(see ). Definition see Let f(t)=Af(t)eiϕf(t)L12(double-struckR;double-struckC) and f ±′ ( t ) be defined by the following non‐tangential limits: f±0.3em(t)limnormalΓ:ztf±0.3em(z),1emzdouble-struckC±, where Γ: z → t denote the non‐tangential limits.…”
Section: Preliminariesmentioning
confidence: 99%
“…Now, we recall the definition of HS derivative for a signal fL12(double-struckR;double-struckC)(see ). Definition see Let f(t)=Af(t)eiϕf(t)L12(double-struckR;double-struckC) and f ±′ ( t ) be defined by the following non‐tangential limits: f±0.3em(t)limnormalΓ:ztf±0.3em(z),1emzdouble-struckC±, where Γ: z → t denote the non‐tangential limits. Then the HS derivatives (or ‘HS derivative’) fd(t),Afd(t), and ϕfd(t) of f ( t ), A f ( t ), and ϕ f ( t ) are defined, respectively, by fd(t)f+(t)+f(t), Afd(t){Af(t)Ref+(t)+f(t)f+(t)+f(t)iff(t)0,...…”
Section: Preliminariesmentioning
confidence: 99%